Coda-avoiding : some Evidence from Portuguese - Veloso, João (2008)
Romance languages are known to be more restrictive than Germanic languages as far as segmental coda-filling is concerned. Moreover, it is also known that within the Romance family some languages have more restrictive constraints ruling coda-filling than others. This paper deals with the specific question of segmental coda-filling in Portuguese. Looking at a large array of different historical phenomena, it is claimed that avoiding any segmental material in coda position corresponds to a very strong tendency of Portuguese phonology which is surfaced under several manifestations. A typological distinction is then proposed here on the basis of the ranking of AVOIDCODA as a prosodic constraint. Such distinction allows not only the differentiation among Romance languages but also between European and Brazilian Portuguese, since Brazilian Portuguese seems to be even more restrictive than European Portuguese in this particular respect.